Congenital hand anomalies and rare syndromes in children - Deepa Shetty; Paras Patel; Rohan Shetty; Sanjay Vansh (International Journal of Contemporary Pediatrics, 2023)
Congenital hand anomalies and associated rare syndromes in children are commonly seen in clinical practice and require complete clinical, radiological and genetic evaluation. The purpose of this case series is to describe four rare syndromic children with varied hand anomalies and differences. Three of the children are female and one is a male. Distal limb defects from simple polydactyly, clinodactyly to cleft hand were identified including preaxial anomalies. Significant clinical problems noted were chiefly cosmetic and altered self-image was also noted in one child. The orofacial clefting noted in the child with ectrodactyly ectodermal dysplasia (EEC) syndrome required repeated surgery though the child had minimal feeding difficulty and significant speech delay. Multidisciplinary management is necessary with the early involvement of clinical geneticist.